1994
DOI: 10.1097/00000658-199406000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Subclavian Revascularization A Quarter Century Experience

Abstract: ObjectiveTwenty-five years of experience with subclavian revascularizations were reviewed to determine the long-term patency rates of different extrathoracic approaches. Summary Background DataAlthough it is generally agreed that proximal subclavian stenosis should be treated by an extrathoracic route whenever possible, the optimum procedure is debated. Alternatives include subclavian carotid bypass, subclavian-to-subclavian or axilloaxillary bypasses, and the authors' preferred technique of subclavian carotid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(32 citation statements)
references
References 7 publications
0
31
0
1
Order By: Relevance
“…Invasive options include carotid-subclavia bypass (CSB), carotid-subclavia transposition (CST), and axillo-axillary bypass. [23][24][25][26] With this presentation we would like to describe the realization of complex radiological interventional therapeutic procedures of treating subclavia steal syndrome and stenosis of the left common iliac artery, at the institute of Radiology KCUS under the supervision of a Bosnian expert Dr. Suad Jaganjac working at the Hamburg Klinik Eilbek in Germany.…”
mentioning
confidence: 99%
“…Invasive options include carotid-subclavia bypass (CSB), carotid-subclavia transposition (CST), and axillo-axillary bypass. [23][24][25][26] With this presentation we would like to describe the realization of complex radiological interventional therapeutic procedures of treating subclavia steal syndrome and stenosis of the left common iliac artery, at the institute of Radiology KCUS under the supervision of a Bosnian expert Dr. Suad Jaganjac working at the Hamburg Klinik Eilbek in Germany.…”
mentioning
confidence: 99%
“…Some studies on surgical treatment and outcomes in subclavian artery stenosis reported a perioperative mortality rate of 0-1.8%, ischemic complication rate of 0-8%, and a fiveyear primary patency rate of 83-95% [4][5][6][7][8] . With surgical treatment, although the incidence is low, perioperative complications and mortality, as well as symptom recurrence, have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, surgical revascularization has been the preferred treatment option with acceptable long-term results [5]. However, over the last two decades, endovascular therapy of localized supra-aortic vessel disease becomes an established therapy [6,7].…”
Section: Introductionmentioning
confidence: 99%